Suture Repair of a Pole Patella Fracture. (August 2017) - Swensen, Stephanie; Fisher, Nina; Atanda, Abiola; Egol, Kenneth A.
Abstract : Purpose: Operative fixation of displaced patella fractures is considered to be standard of care. However, patients with inferior pole patella fractures have limited options in terms of fixation. This video demonstrates the repair of an inferior pole patella fracture using nonabsorbable suture fixation. Methods: Suture repair of patella fractures is a clinically acceptable technique, yielding similar functional results to patella fractures treated with K-wires or cannulated screws while reducing the rates of removal of hardware after fixation. Results: This video features the repair of a displaced, comminuted inferior pole patella fracture using 5 Ethibond and Fiberwire. Postoperative radiographs confirm bony union. Conclusions: Suture fixation for pole patella fractures provides reliable fixation and reduces the risk of postoperative complications secondary to hardware irritation. This case highlights the success of this technique.